Catheter‐induced premature ventricular complexes (PVCs) may aid in the determination of optimal timing for clinical PVC ablation. Issue 12 (17th November 2019) - Demir, Serdar; Akgun, Taylan; Gulsen, Kamil; Kup, Ayhan; Uslu, Abdulkadir; Kayan, Fethullah; Kepez, Alper
Abstract: Background: The aim of the present study is to evaluate whether catheter‐induced premature ventricular complexes (PVCs) produced at the presumptive ablation site may aid in the identification of the optimal timing of the earliest local activation for the successful ablation of clinical PVCs. Methods: Sixty‐three consecutive patients (35 males, age: 53.5 ± 14.4 years) without any exclusion criteria who had undergone PVC ablation between 1 July 2018 and 1 July 2019 constituted our study population. The time interval between the beginning of the EGM and the beginning of the QRS of each catheter‐induced PVC (Cath EGM‐ECG) and the time interval between the beginning of the EGM of clinical PVCs at the earliest site and the beginning of the QRS of clinical PVCs (PVC earliest EGM‐ECG) were noted for each patient. The value of Cath EGM‐ECG as a reference for procedural success of ablation was evaluated by examining the relationship between Cath EGM‐ECG and PVC earliest EGM‐ECG. Results: Fifty‐two patients had successful ablation, and 43 of them (82.7%) had PVC earliest EGM‐ECG values greater than or equal to Cath EGM‐ECG. Eleven patients had procedural failure, and all of them had PVC earliest EGM‐ECG values lower than Cath EGM‐ECG. A PVC earliest EGM‐ECG value –1.5 ms greater than Cath EGM‐ECG predicted successful ablation with a sensitivity of 90.4% and a specificity of 100.0% in the general patient population. Conclusion: Cath EGM‐ECG seems to serve as a reliable guide for finding the optimal timing of the earliest site for successful PVC ablation.